The Efficacy of Task-Based Mirror Therapy for Upper Limb Motor Function in Stroke Patients: A Meta-Analysis of Randomized Controlled Trials - Zhou, Hang; Zhang, Zhen; Li, Renpeng; Xu, Yousong; Bai, Jingyang (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2022)
Introduction The efficacy of task-based mirror therapy for upper limb motor function remains controversial in stroke patients. We conduct a systematic review and meta-analysis to explore the influence of task-based mirror therapy on upper limb motor function in stroke.Methods We have searched PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases through August 2021 for randomized controlled trials (RCTs) assessing the effect of task-based mirror therapy on functional improvement in stroke. This meta-analysis is performed using the random-effect model.Results Six RCTs are included in the meta-analysis. Overall, compared with conventional rehabilitation for stroke, task-based mirror therapy significantly improved Fugl-Meyer Assessment (MD=4.60; 95% CI=1.15 to 8.06; P=0.009), and obtained the comparable impact on Modified Barthel Index (MD=4.96; 95% CI=−4.44 to 14.35; P=0.30), grip strength (MD=3.74; 95% CI=−1.61 to 9.09; P=0.17), modified Ashworth Scale (arm, MD=0.34; 95% CI=−0.67 to 1.35; P=0.50) and modified Ashworth Scale (hand, MD=0.10; 95% CI=−0.58 to 0.77; P=0.78).Conclusions Task-based mirror therapy is effective to improve upper limb motor function in stroke patients.
Keywords: task-based mirror therapy; upper limb motor function; stroke; randomized controlled trials; meta-analysis.